Islam and the legal system of Malaysia - Shuaib, Farid Sufian; Bari, Abdul Aziz (The Malaysian Current Law Journal, 2011)
Issues pertaining to Islam and the legal system of Malaysia, including particularly that of her constitutional system, need to be seen within the right context. One also need to understand the composition as well as the nature of the legal system, including its origin and developments, ever since civilization started in the country. All these mean that one has to see the issue beyond the days when English law principles began to be applied in this land. It goes without saying that, although Malaysia is part of the common law world, English common law is just one of the sources whose application is subject to certain limitations. It is to be emphasized that the whole exercise is to put everything in the right and proper place and context. Consequently, this discourse is not a revisionist agenda seeking to rewrite the Constitution or the legal system.